Determination of electrolyte composition of saliva and calcium level in blood of children with bronchial asthma - Shumna, T. Ye.; Voznyi, O. V.; Lepetchenko, Ye. S.; Шумна, Таміла Євгенівна; Возний, Олександр Вікторович; Лепетченко, Єлизавета Станіславівна (My University, 2020)
Aim of the study: Тo analyse the individual biochemical parameters and pH of saliva and content of calcium in the blood of children with bronchial asthma. Material and methods: The examination of patients was carried out in the Municipal Non-Commercial Enterprise City Children’s Hospital no. 5 in Zaporizhia City Council and the University Clinic of Zaporizhzhia State Medical University. The main study group comprised 49 children aged 5 to 17 years with bronchial asthma, who were taking inhalation glucocorticosteroids for basic control treatment. The comparison group consisted of 29 children without burdened allergic anamnesis. The results were processed in Microsoft Excel for Windows 4.0 and Statistica 6.0. Results: The level of total calcium in the blood of the children of the main group was equal to 2.33 (2.24; 2.39), while in the children of the comparison group it was equal to 2.51 (2.42; 2.55) at p < 0.001. This was also characterised by a decrease in the amount of ionised calcium determined in saliva: 0.55 (0.45; 0.69) in the main group versus 0.86 (0.75; 0.94) in the comparison group, at p < 0.001. When determining the saliva pH, the data obtained indicated a shift of indicators toward an increase in acidity in the main group: 6.90 (6.88; 7.10) with stable indicators 7.13 (6.87; 7.32) in the control group at p = 0.015. A slight difference between the obtained data was also found when comparing the chlorine ion content in saliva: 28.6 (25.9; 32.0) in the main group versus 32.2 (28.1; 34.7) in the control group, at p = 0.048. The inverse relationship between the levels of potassium ions and saliva pH was detected (–0.31 in the main group and –0.37 in the comparison group). Conclusions: Our study confirms the presence of changes in the electrolyte composition of saliva and the content of calcium in the blood of children with bronchial asthma on the background of taking inhalation glucocorticosteroids.
Keywords: children; calcium; bronchial asthma; electrolytes